2023
DOI: 10.3389/fnut.2023.1170992
|View full text |Cite
|
Sign up to set email alerts
|

Association between ultra-processed food intake and risk of colorectal cancer: a systematic review and meta-analysis

Abstract: BackgroundAlthough some epidemiological studies have shown a positive relationship between high intake of ultra-processed food (UPF) and risk of colorectal cancer (CRC), the results remain inconsistent. Therefore, we conducted this systematic review and meta-analysis to clarify the association between UPF intake and CRC risk.MethodsPubMed/MEDLINE, Web of Science, EMBASE, China National Knowledge Infrastructure (CNKI) and Wan fang databases were used to search the relevant studies published up to February 2023.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 52 publications
0
6
0
Order By: Relevance
“…However, despite the general trend in studies indicating a relationship between UPF consumption and CRC, supported by recent meta-analyses by Isaksen and Dankel (2023) and Largo et al ( 2023) [35,[54][55][56], other studies produce contradictory results. This is because there are other relevant factors that can significantly influence the acquisition of healthy habits.…”
Section: Discussionmentioning
confidence: 99%
“…However, despite the general trend in studies indicating a relationship between UPF consumption and CRC, supported by recent meta-analyses by Isaksen and Dankel (2023) and Largo et al ( 2023) [35,[54][55][56], other studies produce contradictory results. This is because there are other relevant factors that can significantly influence the acquisition of healthy habits.…”
Section: Discussionmentioning
confidence: 99%
“…According to the NOVA classification system, all foods and beverages were classified into four groups, including unprocessed/minimally processed food, processed culinary ingredients, processed food and UPFs ( 11 ). The UPFs are usually ready-to-eat, hyper-palatable, cheap and characterized by high in energy density, salt, fats, added sugar and low in fiber, vitamins and minerals ( 13 ). Examples of UPF included sugar-sweetened drinks, sweet, crisps, cookies and cakes, and many ready-to-heat products such as pizza, burgers, noodles and desserts.…”
Section: Methodsmentioning
confidence: 99%
“…Thus far, many epidemiological studies have shown the significant positive associations between high UPF consumption and increased risks of various diet-related chronic non-communicable diseases, such as overweight/obesity, type 2 diabetes, cardiovascular disease (CVD), and certain cancers (14)(15)(16)(17). Moreover, multiple previous systematic reviews and meta-analyses have also confirmed these positive associations (13,18,19). Notwithstanding, only a few epidemiological studies have specially explored the potential relationship between UPF consumption and the risk of CKD (20-27).…”
Section: Introductionmentioning
confidence: 93%
See 1 more Smart Citation
“…Worldwide, the consumption of UPFs has experienced a rapid increase, representing more than half of the daily calories consumed in high-income countries (3,7,8). Similarly, in low-and middleincome countries, a sustained growth in the sale of these products and their contribution to energy intake is observed (4,9).…”
Section: Introductionmentioning
confidence: 99%